Evaluation of hand functions and distal radioulnar joint instability in elite wheelchair basketball athletes: a cross-sectional pilot study - Yuine, H.; Mutsuzaki, H.; Yoshii, Y.; Shimizu, Y.; Ishida, N.; Yasuda, T.; Iwai, K.; Hotta, K.; Shiraish, H.; Tachibana, K. (BMC Sports Science, Medicine and Rehabilitation, 2023)
Background Wrist injury affects wheelchair basketball players` performance; however, the relationship between distal radioulnar joint (DRUJ) instability and hand functions is unclear. This cross-sectional pilot study investigated DRUJ instability in elite female wheelchair basketball athletes using force-monitor ultrasonography.